Assessment of the Diagnosis-To-Needle Times for Patients Admitted to the Emergency Department with Acute ST-Segment Elevation Myocardial Infarction - Çon Enes; Yılmaz Ahmet; Süygün Hakan; Muştu Mehmet; Avcı Ali (Journal of Cardiovascular Emergencies, 2024)
Coronary artery disease is one of the most common causes of death in the world. The outcome of patients with ST-elevation myocardial infarction is influenced by many factors, and the time elapsed from symptom onset to diagnosis and reperfusion have a critical role in this regard.